2012
DOI: 10.4236/jct.2012.36139
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Expression in Cervical Cancer and High Grade Squamous Intraepithelial Lesions

Abstract: Objectives: The finding of new prognostic factors in human cervix cancer is necessary to improve present conventional treatments. The aim of the present study was to determine the expression and evaluate the prognostic value of hypoxia-inducible factor-1(HIF-1α), vascular endothelial growth factor (VEGF) and eritropoyetin receptor (EpoR) in cervix cancer stages IIA-IIB and in preinvasive high grade squamous intraepithelial lesions (HSIL) Methods: The study included 70 patients with cervix cancer, FIGO stages I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…High/medium expression of HIF-1α and VEGF in proliferating basal-parabasal layers of normal-cervix were seen compared to spinous layer (Table1). Similar, high/medium expression of VEGF was reported earlier in the basal-parabasal layers of normal cervical epithelium contrary to low expression of HIF-1α (6).No significant difference in expression profiles of these genes in normal cervical epithelium were seen with respect to HPV16 infection. Thus, it can be suggested that high expression of HIF-1α and its target protein VEGF in basal-parabasal layers of normal cervical epitheliums might be due to the reduced expression of VHL.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…High/medium expression of HIF-1α and VEGF in proliferating basal-parabasal layers of normal-cervix were seen compared to spinous layer (Table1). Similar, high/medium expression of VEGF was reported earlier in the basal-parabasal layers of normal cervical epithelium contrary to low expression of HIF-1α (6).No significant difference in expression profiles of these genes in normal cervical epithelium were seen with respect to HPV16 infection. Thus, it can be suggested that high expression of HIF-1α and its target protein VEGF in basal-parabasal layers of normal cervical epitheliums might be due to the reduced expression of VHL.…”
Section: Discussionsupporting
confidence: 86%
“…Unlike expression pattern of LIMD1 and VHL during different stages of CACX, the expression of HIF-1α and VEGF were high as seen in basal-parabasal layers of normal-cervix (Table 1,Figure 1). Similar expression profiles of HIF-1α and VEGF have also been reported in CACX, HNSCC and colorectal cancer(6,22,23). The inverse correlation of LIMD1 and VHL expression with that of HIF-1α and VEGF was validated by demethylation experiments using 5-aza-dC in HeLa and SiHa cell lines(Figure 3).…”
supporting
confidence: 78%
See 2 more Smart Citations